Development Strategy of Lahendong Pine Forest Tourism Attraction in Tomohon City, North Sulawesi Province - Reyka Irlia Pollah; Yayu Indrawati; I Gusti Ngurah Widyatmaja (International journal of technology and education research, 2024)
This study aims to identify the existing conditions of tourism in the tourist attraction of the Hutan Pinus Lahendong and suggest an effective development strategy in the development of the tourist attraction of the Hutan Pinus Lahendong. The research approach used is qualitative descriptive and supported by quantitative data. Data collection through observation, in-depth interviews, questionnaires, documentation and literature studies. The data analysis used includes the IFE, EFE, IE, and SWOT matrix. The results of the study show that the tourist attraction of the Hutan Pinus Lahendong has the potential to be developed based on the 6A components (Attraction, Accessibility, Amenities, Ancillary Service, Accomodation, and Activities). In addition, there are ten key factors, both internal and external factors. The IE matrix shows that the position of the Hutan Pinus Lahendong tourist attraction is in quadrant five. The SWOT analysis shows that there are 5 alternative strategies that can be proposed in the development of the Hutan Pinus Lahendong tourist attraction, The strategies include: (SO) Optimizing Sustainable Development and Increasing the Promotion of Tourist Attractions, (ST) Improving Environmental Quality, (WO) Improving Tourism Support Facilities, and (WT) Optimizing Cooperation with Stakeholders. Based on the results of the research, it can be suggested that the stakeholder components involved in the development of the Hutan Pinus Lahendong tourist attraction can strengthen cooperation in carrying out tourism attraction development programs appropriately and efficiently.